Manajemen Pendidikan Anak Usia Dini Berbasis Alam TK Al Karim School - Budi Iswanti (El-Idare, 2022)
Management of early childhood education is needed to ensure the learning process goes according to the concept of early childhood education. Nature-based early childhood education management at Al-Karim School Kindergarten includes planning, organizing, implementing, and evaluating stages. This study uses a qualitative approach. The selected research sources were kindergarten principals, teachers, and parents. To obtain the necessary data researchers used data collection techniques, namely interviews, observation and documentation. The results of research related to the management of nature-based early childhood education at Al-Karim School Bandar Lampung Kindergarten include: 1) Planning, at this stage the preparation of semester, weekly and daily programs is carried out. 2) Organizing, at this stage selection and development of themes and indicators appropriate to natural schools are carried out. 3) Implementation, at this stage the educational process is carried out outside the room/classroom with habits to instill commendable morals, independence, logic and likes to share/benefit others. 3) Evaluation, at this stage it is carried out every day and at the end of the semester by the teacher/facilitator which is a process of mapping children's interests and talents.